Efforts to Improve Students’ Learning Interest By Writing Summaries of The Contents of Narrative Essay of Class VIII State Middle School 1 Sosopan - Nurasma; Sutikno (International Journal of Educational Research Excellence (IJERE), 2025)
Summarizing the content of narrative essays is very important for students to simplify and clarify a reading text that is too long. The higher the students' summarization ability, the higher their level of understanding of the content delivered. However, most students have deficiencies in mastering summarization. The purpose of this study is to increase students' interest in learning by writing narrative essay contents. The subjects of this study were students in class VIII SMP Negeri 1 Sosopan academic year 2024-2025consisting of 40 students. The sample in this study was defined as individuals/students from the entire population studied. The method used in this study was classroom action research (CAR).  To analyze the data, classroom action research was conducted through cycles I, II, and III. Through the stages: classroom action plan, implementation, observation, and reflection according to the learning implementation plan (RPP) and syllabus applied in the learning curriculum in State Junior High School 1 Sosopan. Based on data from 40 class students VIII SMP Negeri 1 Sosopan academic year 2024-2025 obtained the percentage of student learning completion classically in cycle I of 75% of the total number of students who completed 30 people, while those who did not complete 10 people, in cycle II of 82.5% of the total number of students who completed 33 people, while those who did not complete 7 people, and cycle III of 95% of the total number of students who completed 38 people, while those who did not complete two people. Thus, it is clear that students' interest in learning by summarizing the content of narrative essays is included in the good or increasing category.